The potential of waste microalgal hydrolysate for power generation in enzymatic fuel cell. (20th June 2018) - Lee, Ja Hyun; Kim, Dong Sup; Yang, Ji Hyun; Yoo, Hah Young; Han, Sung Ok; Lee, Jinyoung; Park, Chulhwan; Kim, Seung Wook
Abstract: The purpose of this study is to generate power by using the waste hydrolysate from microalgal extracts (AH), substrates of enzymatic fuel cell (EFC), and analyze the effects of microalgal hydrolysate containing a neutralizing agent on EFC. The effect of different dilute acids on extraction of microalgae was also investigated. The maximum concentration (∼5 g/L) of extraction was achieved for Chlorella pyrenoiudosa under the optimum conditions (2% hydrochloric acid and 100 g/L biomass loading). In order to investigate the effects of various neutralization agents used for AH on the EFC system, CV and EIS were investigated. Higher current and lower resistance values appeared during the neutralization using KOH. Maximum power density of 3637 μW/cm 2 was obtained for the EFC system, 6.59 folds higher than the control. The result implies that AH used as a substrate has a significant influence on the power generation in the EFC system. Graphical abstract: Image 1 Highlights: Hydrolysis of C. pyrenoidosa was performed by acid-thermal extraction. The most effective acid for hydrolysis was determined as 2% HCl. The AH obtained from C. pyrenoidosa was utilized in the EFC system. AH showed 3637 μW/cm 2 power density at a current density of 10.34 mA.